Pengaruh Perputaaran Persediaan, Total Asset Turnover, Struktur Modal terhadap Pertumbuhan Laba dengan Ukuran Perusahaan sebagai variabel moderasi - Yusniar, Vrisca; Jayanih, Ahmad; Hidayat, Imam; Abbas, Dirvi Surya (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This research aims to determine the effect of inventory turnover, total asset turnover, capital structure on profit growth with company size as a moderating variable in food and beverage manufacturing sub-sector companies industry for the 2020-2024 period for 5 years. This sampling technique uses purposive sampling, and produces a sample of 10 companies so that there are 50 observation samples. The data used are secondary data obtained from the Indonesia Stock Exchange website. The analysis used in this study is panel data regression. This study uses Eviews12. The results of the study indicate that: 1) Inventory Turnover affects Profit Growth; 2) Total Asset Turnover affects Profit Growth; 3) Capital Structure does not affect Profit Growth; 4) Inventory Turnover can moderate the relationship between Company Size and Profit Growth; 5) Total Asset Turnover can moderate the relationship between Company Size and Profit Growth; 6) Capital Structure can moderate the relationship between Company Size and Profit Growth.